Pandemic predisposing influence for feline lower urinary disorders - Paulino, Carolina C. L.; Meneses, André; Almeida, Pedro; Dinis, Paulo; Tavares de Oliveira, Joana (Frontiers in Veterinary Science, 2025)
Lower urinary tract signs (LUTS) in cats encompass a range of clinical symptoms, that may have been altered by the unique circumstances of confinement and increased human interaction during the lockdowns associated with the COVID-19 pandemic. The stress of confinement could exacerbate underlying behavioral issues, while increased caregiver presence might influence the expression of LUTS, potentially leading to either improved monitoring and early detection or increased stress-related symptoms. This study aimed to evaluate the impact of the COVID-19 pandemic on the presentation and outcomes of LUTS in cats by examining the potential influence of increased caregiver presence and confinement-related stress on clinical manifestations and disease progression. This retrospective study reviewed 298 cats with LUTS seen at a veterinary hospital from 2019 to 2021. Inclusion criteria required a complete set of examinations, including urinalysis, imaging, and urine culture. Cats were divided into a before-pandemic (BP) group and a during-pandemic (DP) group. Key variables, such as urethral obstruction, recurrence rates, and mortality, were statistically analyzed. The DP group demonstrated a statistically significant decrease in relapses (p < 0.001) and mortality (p < 0.05) compared to the BP group. Despite a rise in urethral obstructions in the DP group (p = 0.036), there was an overall reduction in adverse outcomes. BP cats were more likely to experience multiple episodes of LUTS than DP cats (p < 0.01). The findings suggest a positive impact of caregiver presence during the pandemic on LUTS outcomes, possibly due to improved monitoring and timely intervention. These insights underscore the potential benefits of increased caregiver engagement in managing feline LUTS.